Paphiopedilum charlesworthii var. lannaense, a new slipper orchid from Northern Thailand identified by morphological and AFLP analyses - Tongkham, Wicharuj; Pumikong, Supalak; Potapohn, Nuttha; Bundithya, Weenun (Phytotaxa, 2022)
A new endemic slipper orchid in the family Orchidaceae from Northern Thailand was described according to morphological and molecular analyses. Morphological information specifies the new slipper orchid Paphiopedilum charlesworthii var. lannaense to be similar to Paphiopedilum charlesworthii (Rolfe) Pfitzer 1895, with the exception of its staminode being obovate-obcordate with yellow color, glittery and rough surface. Molecular analysis by AFLP technique indicates that Paphiopedilum charlesworthii var. lannaense can be included as a member of section Paphiopedilum and is closely related to Paphiopedilum coccineum Perner, H. & Herrmann, R. (2000) (syn. Paphiopedilum barbigerum var. coccineum), from which it differs morphologically by dorsal sepal and petal characters. The morphological and molecular evidence supported that Paphiopedilum charlesworthii var. lannaense is a new slipper orchid in the genus Paphiopedilum (Cypripedioideae, Orchidaceae).